The ERA-EDTA today and tomorrow: a progress document by the ERA-EDTA Council - Zoccali, Carmine; Arici, Mustafa; Blankestijn, Peter J; Bruchfeld, Annette; Capasso, Giovambattista; Fliser, Danilo; Fouque, Denis; Goumenos, Dimitrios; Ketteler, Markus; Malyszko, Jolanta; Massy, Ziad; Rychlík, Ivan; et al. (Clinical kidney journal, 2018)
Scientific societies are increasingly seen as central to the advancement of information sharing and collaboration among scientists and clinical investigators for the progress of medical research and the promotion of education, professional competence, integrity and quality studies. To more effectively serve the practicing nephrologists and investigators dedicated to renal science, the Council of the European Renal Association and European Dialysis and Transplantation Association (ERA-EDTA) reorganized and integrated the various activities of the society into two branches, the Clinical Nephrology Governance branch and the Renal Science branch. New affordable initiatives to promote research, education and professional development and to advocate for the recognition of chronic kidney disease as a major public health issue at the European level will be put in place and/or potentiated in the new organizational frame. Educational initiatives will be espoused to Continuous Professional Development and, starting from 2019, 14 Education & Continuous Professional Development courses will be held covering the full range of knowledge areas of modern nephrology. Consolidation and development is the short- and medium-term mantra of the ERA-EDTA. The society has a rich portfolio of successful activities and brilliant, creative scientists among its members. Integrating the various activities of the ERA-EDTA and treasuring the expertise and wisdom of its most accomplished members will facilitate collaborative research, education and its public impact at large.
Keywords: scientific societies; ERA-EDTA; clinical governance; scientific associations